Age Takes Hold of Us by Surprise: Conceptualizing Vulnerabilities in Aging as the Timing of Adverse Events. (26th July 2019) - Vanhoutte, Bram
Abstract: Objectives: Aging in the public eye can be distilled to a limited number of adverse events, such as loss of health, partnership and wealth. While these events are a constitutive part of "normal aging, " they do not occur uniformly at the same time point in the life course. This study investigates to what extent bereavement, functional health loss, and onset of poverty are adequate markers of aging, and illustrates inequalities in their timing according to cohort, gender, class, education, and ethnicity. Methods: The English Longitudinal Study of Ageing (ELSA), collected over seven waves (2002–2016) ( n = 7, 890) is examined in an event history framework. Cox proportional hazard models are used with the Andersen Gill extension in case of multiple failures per respondent. Results: Persistent associations of lower occupational class, lower education, and having a black or minority ethnic background are found with increased hazards of functional health loss and wealth loss. Earlier born cohorts have lower hazards for functional health loss, wealth loss, and bereavement. Women have higher hazards for bereavement, and lower hazards for wealth loss. Discussion: The timing of adverse events is a crucial gateway through which existing social inequalities are transferred into unequal aging pathways.